Role and therapeutic potential of E3s in the tumor microenvironment of hepatocellular carcinoma - Wang, Hailin; Li, Qiang; Tang, Qinqin; Shi, Gang; Wu, Guo; Mao, Xingbo; Wu, Changkang; Zhang, Lixin; Liu, Jie; Li, Jingdong; Li, Bo (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is a high-incidence, poor-prognosis malignancy worldwide, requiring new strategies for treatment. Ubiquitination, especially ubiquitination through E3 ubiquitin ligases, plays an indispensable role in the development and progression of HCC. E3 ubiquitin ligases are crucial enzymes in ubiquitination, controlling the degradation of specific substrate proteins and influencing various cellular functions, such as tumor cell proliferation, apoptosis, migration, and immune evasion. In this review, we systematically summarize the mechanisms of E3 ubiquitin ligases in HCC, with a focus on the significance of RING, HECT, and RBR types in HCC progression. The review also looks at the potential for targeting E3 ligases to modulate the tumor microenvironment (TME) and increase immunotherapy efficacy. Future studies will optimize HCC treatment by formulating specific inhibitors or approaches that will be based on gene therapy targeting E3 ligases in order to overcome resistance issues with present treatments and create optimism in the journey of treatment for HCC patients.